A proposed ground motion selection and scaling procedure for nonlinear response history analysis - Zengin, Esra. (Thesis (Ph.D.)-Bogazici University.Kandilli Observatory and Earthquake Research Institute, 2016., 2016)
With the advancement in performance-based earthquake engineering, nonlinear response history analysis of structures has become more common in recent years. The selection and scaling of ground motions for use in nonlinear response history analysis is one of the most critical steps in performance-based seismic assessment procedures. This study presents ground motion selection and scaling procedure that addresses the uncertainty in the spectral demand with the preserved dispersion within the ground motion set. The candidate ground motion sets are constructed based on dispersion statistics about the target spectral demand. The optimum ground-motion set is linearly scaled by using an optimization algorithm that minimizes the error between scaled median and target spectra. The scaling stage ensures that the median record spectrum provides a reasonable match to target median in a previously defined period interval. This procedure allows performing further modification on each scaled ground motion in order to match the target variance of the scenario-based spectrum. In this study, a novel probabilistic framework is presented to propagate the uncertainties in both ground motion intensity and the structural response on fragility curve estimations. To investigate the effects of uncertainties on seismic damage estimations, the results of this study are compared with those obtained by the conventional fragility curve approach.
Keywords: Earthquake engineering.; Nonlinear systems.